Detection of Phenuiviridae, Chuviridae Members, and a Novel Quaranjavirus in Hard Ticks From Danube Delta - Bratuleanu, Bianca Elena; Temmam, Sarah; Munier, Sandie; Chrétien, Delphine; Bigot, Thomas; van der Werf, Sylvie; Savuta, Gheorghe; Eloit, Marc (Frontiers in Veterinary Science, 2022)
Ticks are involved in the transmission of various pathogens and several tick-borne diseases cause significant problems for the health of humans and livestock. The members of Quaranjavirus genus are mainly associated to argas ticks but recent studies demonstrated the presence of novel quaranjaviruses-like in ixodid ticks. In 2020, 169 Rhipicephalus sp. ticks were collected in Southern Romania from small ruminants and analyzed by high-throughput transcriptome sequencing. Among the viral families infecting Romanian ticks, we identified sequences from Phenuiviridae (Brown dog tick phlebovirus 1 and Brown dog tick phlebovirus 2) and Chuviridae families (Cataloi mivirus), and numerous sequences from a new quaranjavirus-like, tentatively named Cataloi tick quaranjavirus (CTQV). Phylogenetic analyses performed on the five segments show that CTQV is phylogenetically positioned within a clade encompassing Ixodidae-borne viruses associated with iguanas, small ruminants, seabirds and penguins distributed across different geographical areas. Furthermore, CTQV positioned differently depending on the segment considered. This is the first report on the detection of a quaranjavirus-like in Eastern Europe. Further investigations are needed to discern its infectivity and pathogenicity against vertebrates.